2017
DOI: 10.1101/141135
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-specific prevalence of anti-Pgp3 antibodies and severe conjunctival scarring in the Solomon Islands

Abstract: BackgroundTrachomatous trichiasis (TT) and ocular Chlamydia trachomatis (Ct) infection in the Solomon Islands are scarce, whereas trachomatous inflammation–follicular (TF) is prevalent.MethodsWe enrolled 1511 people aged ≥1 year from randomly selected households in 13 villages in which >10% of the population had TF prior to a single round of azithromycin MDA undertaken six months previously. Blood was collected from people of all ages to be screened for anti-Pgp3 antibodies. Photographs were collected from … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The World Health Organization guidelines for implementing mass drug administration (MDA) are based largely on TF prevalence. We have previously argued that whilst the Solomon Islands has sufficiently prevalent clinical signs (TF) of trachoma to qualify for implementation of MDA, the prevalence of infection and trichiasis [ 3 , 5 ], as well as severe scarring and serological signs of prior infection [ 6 ] are all too low to suggest that clinical diagnosis with TF has the necessary specificity to be used as an indicator of need for intervention in this population. By showing that the transcriptional profile of TF ( Ct uninfected) cases in the Solomon Islands share some, but not all, the components of typical trachoma responses seen elsewhere, the current findings add to those of our previous studies to suggest that the majority of TF disease we observe there is not related to Ct .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The World Health Organization guidelines for implementing mass drug administration (MDA) are based largely on TF prevalence. We have previously argued that whilst the Solomon Islands has sufficiently prevalent clinical signs (TF) of trachoma to qualify for implementation of MDA, the prevalence of infection and trichiasis [ 3 , 5 ], as well as severe scarring and serological signs of prior infection [ 6 ] are all too low to suggest that clinical diagnosis with TF has the necessary specificity to be used as an indicator of need for intervention in this population. By showing that the transcriptional profile of TF ( Ct uninfected) cases in the Solomon Islands share some, but not all, the components of typical trachoma responses seen elsewhere, the current findings add to those of our previous studies to suggest that the majority of TF disease we observe there is not related to Ct .…”
Section: Resultsmentioning
confidence: 99%
“…Two years after the initial survey, all individuals in groups D and N were revisited by chance during a serological survey and were tested for evidence of prior Ct infections with an anti-Pgp3 ELISA test [ 5 ]. All members of groups D and N were seronegative at that time, suggesting that no member of either group had previously been infected with Ct .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Around 26% of 1-9 year olds living there had TF, but Ct infection was very scarce at just 1.3%. Using a serological tool we showed that 53/66 (80%) of the cases of TF that we observed were in people who were serologically negative for prior Ct infection 8 . Clinical signs of trachoma were also a poor indicator for the need to deploy antimicrobials in Fiji, where the high prevalence of TT cases could be better explained by socio-epidemiological practices of eyelash depilation than by Ct infections 9 .…”
Section: Introductionmentioning
confidence: 78%